Promoting school lunch fruit and vegetable intake through role modeling: a pilot study - Stephanie S Machado; Michael Burton; Wes Loy; Kyle A Chapman (AIMS Press, 2020)
Objectives: Child fruit and vegetable consumption is a critical component of adult chronic disease prevention, yet fruit and vegetable intake remains low among elementary school children in the United States. This pilot study tested a role modeling intervention designed to promote fruit and vegetable consumption in a U.S elementary school cafeteria setting. Methods: This one-year, repeated cross-sectional study used digital photographs to assess fruit and vegetable waste at baseline (n = 566 trays) and follow-up (n = 231 trays) of kindergarten through fifth grade students in one elementary school. Differences in waste were assessed through Mann-Whitney statistical tests. Feedback on intervention acceptability was provided by the intervention team during implementation. Results: The proportion of students consuming all of their selected fruits and vegetables increased by 11.1% and 8.7% respectively (p < 0.01). There was a significant decrease in the proportion of students not consuming any of their selected fruit (16.0%, p < 0.001). Staff and students provided positive reports of intervention acceptance. Conclusions and Implications: Findings from this pilot study indicate that role modeling in a school cafeteria setting may be a promising health promotion strategy and provide groundwork for future research in the development of school cafeteria role modeling interventions. Further research is needed to assess intervention efficacy and acceptability at a larger scale.